2010
DOI: 10.1007/s12205-010-0838-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a front high hydraulic conductivity zone on hydrological behavior of subsea tunnels

Abstract: This study focuses on the hydrological behavior of the ground ahead of a tunnel face. A localized high hydraulic conductivity zone with high water pressure is denoted as a hazardous zone. To analyze the impact of the hazardous zone on the face stability, a new indicator (TSR: the ratio of the driving force to the resisting force) is proposed on the basis of the "advance core" concept (Lunardi, 2000). A series of three-dimensional steady-state seepage analyses are performed to estimate the distribution of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…When shield tunnel locates under the water table line, the soil excavation often induces underground water seepage and apt to cause the collapse of shield tunnel face. The face stability analysis under seepage condition was studied by numerical simulation [22][23][24] or theoretical analysis which was based on the existing model. Anagnostou and Kovári [25] studied the influence of seepage on the stability of tunnel face based on the wedge model.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…When shield tunnel locates under the water table line, the soil excavation often induces underground water seepage and apt to cause the collapse of shield tunnel face. The face stability analysis under seepage condition was studied by numerical simulation [22][23][24] or theoretical analysis which was based on the existing model. Anagnostou and Kovári [25] studied the influence of seepage on the stability of tunnel face based on the wedge model.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The seepage force acting on the tunnel face can be modeled on the basis of the advance core concept [2,7]. As an advance core, a hypothetical cylinder has the cylindrical shape volume of the ground.…”
Section: Computational Model Of the Seepage Forcementioning
confidence: 99%
“…Hong [1,2] analyzed causes of several tunnel flooding cases and found that the presence of unforeseen high hydraulic conductivity zones with high water pressure (herein, termed as hazardous zones) was strongly associated with various flooding accidents. High water pressure in a fault breccia zone can lead to significant problems related to the stability of the tunnel face.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brekke and Selmer-Olsen 1965;Chang et al 2005;Anagnostou 2010; Zingg and Anagnostou 2012b); specific case histories (e.g. Ko ¨nz 1968;Barla 2000;Bezrodny et al 1992;Dahlø and Nilsen 1994;Nilsen 2010); or specific aspects such as the effect of pre-support (pipe roof) and grouting in fractured zones (Shi et al 2015) or the mechanism of punching failure (Hong et al 2010).…”
Section: Introductionmentioning
confidence: 99%